THE RELATIONSHIP BETWEEN SELF-EFFICACY AND FAMILY RESILIENCE IN PARENTS OF CHILDREN WITH DISABILITIES - Reliani, Reliani; Setiyowati, Indah; Husna, Anis Rosyiatul; Prabawati, Chlara Yunita; Priyantini, Diah; Wijaya, Siswanto Agung (Universitas Airlangga, 2026)
Introduction: Parents raising a child with disabilities experience a range of complex physical, psychological, social, and economic challenges. Internal psychological factors, particularly self-efficacy, often influence a parent's ability to cope with these difficulties. Higher levels of self-efficacy improve a family's capacity to adapt to and recover from the stress of caregiving, a concept known as family resilience. This study aims to explore the relationship between self-efficacy and family resilience among parents of children with disabilities. Method: This study employed a quantitative correlational design with a cross-sectional approach. The study population consisted of 59 parents of children with disabilities, selected using total sampling. Data were collected using a modified self-efficacy questionnaire based on Bandura’s theory and a family resilience questionnaire adapted from Walsh’s model. Data analysis was conducted using Spearman Rank correlation with a significance level of α = 0.05. Results: The findings indicated that the majority of respondents exhibited high self-efficacy (94.9%) and high family resilience (96.6%). A very strong positive correlation was identified between self-efficacy and family resilience (r = 0.809; p < 0.001). Conclusion: The study reveals a strong link between self-efficacy and family resilience in parents of children with disabilities. It underscores the need to enhance parental self-efficacy to boost family resilience when facing caregiving challenges.